Reliability of dynamically measured flexibility matrix on damage detection of frame structures - Monajemi, H.; Abdul Razak, H.; Ismail, Z. (2012)
The use of dynamically measured flexibility matrix to indicate and locate damage is reported in many studies. However their focus is mostly on structures like beams or slabs that each node has one degree of freedom and all DOFs are in the same direction. For a structure with degrees of freedoms in three directions e.g. frame structures, both modal testing and damage detection become more complicated. It is because each DOF in the stiffness matrix is influenced by all the members connected to it. When it comes to flexibility matrix, another problem arises. Since flexibility matrix is more global, damage does not only affect the related DOFs, but others too. This article aims to address these problems in order to develop a reliable damage detection method for frame structures. The modal parameters of a four story frame structure are calculated for intact and damage cases. Changes in the flexibility matrix were analyzed for different damage scenarios when the damage member is known. It was suggested that there are some patterns that relate DOFs and members which can be used to locate the damage member. Â© The Society for Experimental Mechanics, Inc. 2012.